2008
DOI: 10.1590/s0004-27302008000900010
|View full text |Cite
|
Sign up to set email alerts
|

Ponto de corte do índice Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) avaliado pela curva Receiver Operating Characteristic (ROC) na detecção de síndrome metabólica em crianças pré-púberes com excesso de peso

Abstract: RESUMOObjetivo: Estabelecer, entre os pontos de corte do índice homeostatic model assessment for insulin resistance (HOMA-IR), citados na literatura, o melhor em identifi car a síndrome metabólica (SM) em crianças com obesidade e sobrepeso. Métodos: Foram estudadas 140 crianças pré-púberes. A defi nição de SM foi adaptada da International Diabetes Federation. Para cada ponto de corte de HOMA-IR foram estimados sensibilidade e especifi cidade, tomandose como desfecho a SM. Uma curva receiver operating character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 42 publications
5
27
1
5
Order By: Relevance
“…As for skin color variable, 66.2% were nonwhite, corresponding to the findings of Wood et al (2009) [16], whose prevalence ranged from 63.3% in the obese group and 54.8% in the overweight group. Although in this study this variable was not analyzed according to the nutritional status, it appears that the prevalence remains high.…”
Section: Discussionsupporting
confidence: 81%
“…As for skin color variable, 66.2% were nonwhite, corresponding to the findings of Wood et al (2009) [16], whose prevalence ranged from 63.3% in the obese group and 54.8% in the overweight group. Although in this study this variable was not analyzed according to the nutritional status, it appears that the prevalence remains high.…”
Section: Discussionsupporting
confidence: 81%
“…Some authors argue that there is no consensus regarding the ideal HOMA-IR cut-off value in children, and commercially available kits also measure pro-insulin levels (25). However, the HOMA-IR is reliable and practical, since it is standardized for a specific population as we chose, based on that of the study of Madeira and cols., whose data came from a cohort of children of similar age to ours and originating from Rio de Janeiro (15). Furthermore, results of HOMA-IR are strongly correlated with those obtained using the euglycemic hyperinsulinemic clamp (r = 0.82) and are thus considered reliable for epidemiologic studies on a large scale (26,27).…”
Section: Discussionsupporting
confidence: 64%
“…Homeostatic Model Assessment-Insulin Resistance (HOMA-IR) was calculated (14) and the cut-off value ≥ 2.5 was chosen, based on the study of Madeira and cols. (15) in a cohort of the same age from Rio de Janeiro. Glucose and lipid profiles were determined by a colorimetric enzymatic method, using a Hitachi-Roche modular system (Roche Diagnostics GmbH, Mannheim, Germany).…”
Section: Laboratory Evaluationmentioning
confidence: 99%
“…There is still a debate about the appropriate cutoff point for HOMA-IR, with proposed values of ≥2.5,26,27 ≥1.77,28 and >3.16 20. Keskin et al20 found that HOMA-IR was the most sensitive and most specific of three proxies for defining insulin resistance, and the cutoff point for insulin resistance diagnosis based on HOMA-IR was 3.16,20 so that definition was used in the present study.…”
Section: Methodsmentioning
confidence: 94%